Could moderate alcohol intake be recommended to improve vaccine responses?. (July 2014) - Messaoudi, Ilhem; Pasala, Sumana; Grant, Kathleen
<x xml:space="preserve">Abstract</x> The impact of alcohol consumption on human health is complex and modulated by several factors such as patterns and amount of drinking, genetics, the organ system studied, as well as the sex and age of the user. There is strong evidence that chronic ethanol abuse is associated with increased morbidity and mortality, immunosuppression and increased susceptibility to both bacterial and viral infections. In contrast, moderate alcohol consumption exerts positive effects including decreased mortality, and improved cardiovascular disease and insulin sensitivity. Interestingly, accumulating evidence also supports an immune-boosting effect of moderate alcohol. In this editorial, we summarize the findings that support a positive effect of moderate alcohol on host immunity. We also discuss the limitations of the previous data and emphasize the importance of additional studies to uncover mechanisms for these immune-stimulating effects in order to extend these benefits to vulnerable segments of the population who cannot consume alcohol.